Potential of agroforestry for food and nutrition security of small-scale farming households - Omarsherif Mohammed Jemal; Daniel Callo-Concha (University of Bonn, Center for Development Research (ZEF), 2017)
Food and nutrition security is a major global challenge. Enhancing the local production of food is a key alternative in impoverished agrarian countries of the south. One option is agroforestry, promoted and implemented as a land-use system capable of addressing the multifaceted problem of food and nutrition security of small-scale farming households. This paper illustrates the potential roles of local agroforestry practices to contribute to the food and nutrition security of small-scale farming households focusing on the Yayu Coffee Forest Biosphere Reserve in south-western Ethiopia as a case study. The three dominant agroforestry practices, i.e. multistorey coffee systems, homegardens, and multipurpose trees on farmland contribute substantially to the food and nutrition security of households and communities despite each having a particular purpose, species management and composition. Achievement does not depend on individual practices but on their synergistic performance. Multistorey coffee systems mainly generate cash by the sale of coffee beans, non-timber forest products and fuelwood. Crops cultivated under multipurpose trees on farmland produce the major annual food supply of the households, which is generally completed by homegardens that also generate supplementary income. Moreover, several strategies rely on the particular features of the agroforestry systems to meet specific challenges. For instance, the smallscale planting of species such as enset (Ensete ventricosum) to fill the food-shortage season, the cultivation of spices and ritual species to obtain supplementary income, or production of pulses and livestock to secure scarce macro- and micronutrients. Finally, the presence of a variety of edible native species detected in all agroforestry practices, but especially in multistorey coffee systems, evidences an untapped potential that is currently being investigated.
Keywords: 330; food and nutrition security; subsistence farming; traditional agroforestry; wellbeing; Yayu Coffee Forest Biosphere Reserve